Intestinal obstruction and cystic fibrosis: a case report - Aboulfeth, El Mehdi; Abdellaoui, Othmane Alaoui; Bouchentouf, Sidi Mohamed; Bounaim , Ahmed (International Journal of Research in Medical Sciences, 2023)
Distal intestinal obstruction syndrome is one of the frequent digestive complications of cystic fibrosis; due to a more or less complete small bowel obstruction. Proximal intestinal obstruction syndrome is a rarer variant, but has been more often described since the improvement of the management of CF that has led to enhance CF patient survival. We described a 19-year-old male followed in the pediatrics department of the HMIMV for cystic fibrosis complicated by exocrine pancreatic insufficiency and type 1 diabetes, who presented an intestinal obstruction syndrome for two days, consisting on abdominal pain, bloating, bilious vomiting and cessation of stool and gas. Imaging has suspected a mechanical obstruction of the small bowel however no transitional zone could be identified. A conservative treatment was start and because of the inefficiency of this first approach, the decision was made to proceed with a laparotomy. Intra-operatively, a mid-jejunum point with inssipationed stool was noticed to be the transitional aera of the obstruction and conducted us to proceed for an entrotomy and digitaly empty the proximal bowell. PIOS is a more rare intestinal complication but should be considered when the ileo cecal clinical location is absent in an obstruction syndrome. Its treatment is based on laxatives however surgery should wisely be considered in front of failure of the conservative approach or critical condition.